2021
DOI: 10.1111/rec.13456
|View full text |Cite
|
Sign up to set email alerts
|

Floral resource selection by wild bees and honey bees in the Midwest United States: implications for designing pollinator habitat

Abstract: Many seed mix recommendations for creating pollinator habitat are in part based on anecdotal evidence or field observations of bees visiting forbs (i.e. use). However, there is limited information on what forbs are preferred by bees, particularly in working landscapes where bee forage may be limited. We examined floral resource selection by wild bees and honey bees on grasslands in the Midwest using a 5‐year dataset containing over 8,000 plant‐bee interactions. We observed wild bees visiting 83 forb species, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Combining results from which seeded forbs are most often observed blooming and pollinator preference research would identify forb species that (1) readily bloom under realized conditions on private lands, (2) provide high pollinator value, and (3) cost less for private landowners and taxpayers. Our previous work on wild bee and honey bee flower preferences (Simanonok et al 2021) can be combined with our current study to identify forbs that fit these conditions. Out of all non-noxious weed forbs selected by honey bees, all were considered cost-effective in our present study (i.e.…”
Section: Discussionmentioning
confidence: 94%
“…Combining results from which seeded forbs are most often observed blooming and pollinator preference research would identify forb species that (1) readily bloom under realized conditions on private lands, (2) provide high pollinator value, and (3) cost less for private landowners and taxpayers. Our previous work on wild bee and honey bee flower preferences (Simanonok et al 2021) can be combined with our current study to identify forbs that fit these conditions. Out of all non-noxious weed forbs selected by honey bees, all were considered cost-effective in our present study (i.e.…”
Section: Discussionmentioning
confidence: 94%
“…We acknowledge that by doing so, the pollinator network at each site does not include all Apidae pollinators, and consequently may have different nestedness and modularity measurements than networks that include honeybees. However, a recent study conducted in the same region of the United States has demonstrated that in similar restored grassland habitat, honeybees and wild bees had different floral preference and avoidance (Simanonok et al ., 2021). Honeybees were observed to show preferences for the most abundant forbs throughout the season, many of which were introduced species, while native bees were shown to select for another set of forbs, many of which were native species, and their preference varied throughout the season as the floral composition changed.…”
Section: Discussionmentioning
confidence: 99%
“…3a). This is not surprising because these sown flower species are often chosen due to their documented attractiveness to pollinators as 'bee plants' (Harmon-Threatt & Hendrix, 2015;Simanonok et al, 2021), and this contributes to the previously documented success of small-scale restoration projects like pollinator gardens. However, unlike a heavily managed, weeded pollinator garden, in a large-scale reconstruction project like the CP-42 programme, floral sources established in the habitat are not necessarily the intentionally sown 'bee plants'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from California and New Jersey has shown wild bees will readily use, but not necessarily prefer, non-native flowers (Williams et al, 2011). Wild bees in the PPR will visit non-native flowers and even exhibit preference for some, but a majority of the preferred flowers are native (Simanonok et al, 2021). In some cases, non-native…”
Section: Discussionmentioning
confidence: 99%